2021
DOI: 10.1039/d1ra06138k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of graphene/polypropylene composites with high dielectric constant and low dielectric loss via constructing a segregated graphene network

Abstract: The rGO/PP composites with high dielectric constant and low dielectric loss at a low filler content were prepared via constructing a segregated graphene network by encapsulating of GO on PP latex particles and the in situ reduction in GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…We introduced conductive filler ARGO and dielectric ceramic BT simultaneously into PEI substrate. Firstly, the introduced ARGO nanosheets provided adequate polarization centers, as rGO 15,39 or CNTs [40][41][42] did, and contributed largely to the optimized dielectric constant. Secondly, BT nanoparticles enhanced the polarization of ARGO sheets and prevented the formation of leakage current brought by the contacts between ARGO sheets and further optimized the dielectric properties of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…We introduced conductive filler ARGO and dielectric ceramic BT simultaneously into PEI substrate. Firstly, the introduced ARGO nanosheets provided adequate polarization centers, as rGO 15,39 or CNTs [40][41][42] did, and contributed largely to the optimized dielectric constant. Secondly, BT nanoparticles enhanced the polarization of ARGO sheets and prevented the formation of leakage current brought by the contacts between ARGO sheets and further optimized the dielectric properties of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene has excellent electrical conductivity and can be used to modify polymers to prepare high dielectric composites. The common method is to disperse Graphite oxide in polymer solution and then reduce it [1][2][3]. The advantages are that the dispersion is more uniform, and higher dielectric properties can be obtained with less Graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Different reinforcement materials, some mostly preferred inorganic fillers, such as glass fiber (FG), carbon nanotubes, and clays are employed to enhance the properties of the PP polymer. To obtain a high-performance dielectric PP composite, it is reported that an increase in energy storage values is obtained using a blend of maleic anhydride grafted polypropylene (MAPP) and graphene oxide (12). After the increase in use of nanomaterials in the literature, the enhancement of mechanical properties was achieved using PP and 10% nano silica (13).…”
Section: Introductionmentioning
confidence: 99%